Optical properties and 532 nm to 266 nm second harmonic generation in bulk β-BBO crystals grown from the BaB2O4-NaBaBO3-V2O5 system - Simonova, Ekaterina A.; Ezhov, Dmitry M.; Jamous, Ammar Y.; Svetlichnyi, Valerii A.; Kuznetsov, Artem B.; Goreyavcheva, Anastasia A.; Shevchenko, Vyacheslav S.; Kokh, Alexander E. (Proceedings of SPIE)
This article focuses on the top-seeded solution growth (TSSG) of single crystals of the low-temperature noncentrosymmetric modification of barium borate, β-BaB2O4 (β-BBO), using a mixed solvent comprising NaBaBO3 and V2O5. We examine the linear absorption properties across a wide spectral range and nonlinear second harmonic generation (SHG) from 532 nm to 266 nm in β-BBO samples under Nd:YAG laser radiation pumping. The mean linear absorption for ordinary waves in vanadium-based crystals at wavelengths from 300 to 600 nm is found to be an order of magnitude higher than that in standard samples, measuring 0.0059 and 0.0007 cm-1, respectively. However, crystals grown from the proposed vanadium-based solution still exhibit similar SHG efficiency to standard samples. Deviations from the quadratic dependence are observed at pump power densities exceeding 20 MW/cm², possibly attributed to temperature effects resulting from insufficient temperature stabilization.